Darboux transformations of the Supersymmetric BKP hierarchy. Issue 3 (2nd July 2016) - Li, Chuanzhong
Abstract : In this paper, we construct Darboux transformations of the supersymmetric BKP(SBKP) hierarchy. These Darboux transformations can generate new solutions from seed solutions by using bosonic eigenfunctions.